Systemic lupus erythematosus in males: a study of 107 Latin American patients (1996)
Clinical and laboratory features were analyzed in 107 Latin American male patients with systemic lupus erythematosus (SLE) who were compared with a group of 1,209 Latin American female patients with SLE to determine the presence of gender-associated differences. Males had an increased prevalence of renal disease, vascular thrombosis, and the presence of anti-dsDNA antibodies, as well as the use of moderate to high doses of corticosteroids, compared with female SLE patients. Although there was no difference in mortality from all causes, SLE-related mortality was higher in the male group. All these findings are consistent with a more severe disease in Latin American males than in female patients from the same region.